2021
DOI: 10.1108/xjm-10-2020-0186
|View full text |Cite
|
Sign up to set email alerts
|

Work-life balance -a systematic review

Thilagavathy S.,
Geetha S.N.

Abstract: Purpose This study aims to systematically review the existing literature and develop an understanding of work-life balance (WLB) and its relationship with other forms of work-related behavior and unearth research gaps to recommend future research possibilities and priorities. Design/methodology/approach The current study attempts to make a detailed survey of the research work done by the pioneers in the domain WLB and its related aspects. A total of 99 research work has been included in this systematic revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 105 publications
1
5
0
Order By: Relevance
“…Studies conducted by Thilagavathy and Geetha (2021), Smith et al (2011), andUmene-Nakano et al (2013) revealed that there was a significant correlation between work-life balance satisfaction and burnout. Based on the existing literature, the above hypothesis was derived.…”
Section: Hypothesis 2: -Job Burnout Has An Impact On the Work-life Ba...mentioning
confidence: 99%
See 3 more Smart Citations
“…Studies conducted by Thilagavathy and Geetha (2021), Smith et al (2011), andUmene-Nakano et al (2013) revealed that there was a significant correlation between work-life balance satisfaction and burnout. Based on the existing literature, the above hypothesis was derived.…”
Section: Hypothesis 2: -Job Burnout Has An Impact On the Work-life Ba...mentioning
confidence: 99%
“…As per the study on a systematic review of work-life balance related literature, (Thilagavathy and Geetha, 2021) Additional working hours take away the time allocated to spend on the family, intense work results in fatigue and emotional stress which in return will affect the quality of personal/family life. The family aspect considers factors such as the individual's role as father, mother, daughter, son, etc., and family responsibilities such as household work, and taking care of children.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Long work hours and high stress levels not only make it challenging for employees to juggle their work and family responsibilities, but they are also associated with health hazards such as depression, weight gain, and increased consumption of alcohol and tobacco (Babin, 2015). Looking after the work-life balance of an employee improves focus and enhanced productivity (Thilagavathy & Geetha, 2023).…”
Section: Research Questionsmentioning
confidence: 99%